Elevated pulse pressure correlated with reduced retinal peripapillary capillary in thyroid-associated ophthalmology with visual field defect - Ye, Jie; Liu, Weijie; Hu, Xiaozhou; Jiang, Hongxiao; Xu, Mingna; Jin, Haochen; Wang, Mengting; Liu, Zihui; Chen, Qi; Wu, Wencan; Tu, Yunhai (Frontiers in Endocrinology, 2022)
Purpose: To quantify the retinal vessel density in thyroid-associated ophthalmology (TAO) patients with visual field (VF) defect and examine its associations with mechanical and system vascular risk factors for underlying pathogenesis of VF defect in TAO. Methods: The cohort was composed of 62 TAO eyes (39 with VF defect and 23 without VF defect). The pulse pressure (PP), intraocular pressure (IOP), ophthalmic rectus muscular index (MI), superficial retinal capillary plexus (SRCP) and radial peripapillary capillary (RPC) density, and other related parameters were measured. The associations among these factors and VF mean deviation (MD) were analyzed. Results: In TAO patients with VF defect, reduced RPC density, higher PP, larger horizontal and vertical MI were found (All P < 0.03) when compared to TAO patients without VF defect. The RPC density was correlated with VF MD value (r = 0.242, P = 0.029) while SRCP density didn’t (P = 0.419). In univariable general estimating equation (GEE) analysis with RPC density as the outcome, PP and its fluctuation showed significant association (Both P < 0.04). In the final RPC model with multivariable GEE analysis, only PP (β = -0.082, P = 0.029) showed significance while PP fluctuation (P = 0.080) didn’t. Conclusions: The elevated PP was correlated with reduced retinal peripapillary perfusion in TAO resulting in VF defect. These data suggested system vascular factor may be important in pathogenesis of reduced retinal perfusion resulting in visual impairment in TAO.